Implementing of Kurikulum Merdeka: Challenges in Teaching English at SMPN7 Tanjungpinang - Naluri Firmansyah, Bianca; Andri; Farhan Adyatma Zachary; Keti; Erwin Pohan (JET ADI BUANA, 2024)
There have been a lot of articles discussing how the kurikulum merdeka has made significant changes in the education field, some of them addressed the challenges in the implementation. This research focused on the challenges faced by English teachers in SMPN 7 in implementing the curriculum merdeka. This qualitative descriptive research aims to describe in detail the challenges experienced during the process of implementing the curriculum merdeka. Through semi structure interviews, this research proves the challenges experienced by teachers such as the difficulty of implementing differentiated learning due to the large number of students, the lack of technological skills for the digitise learning, and the differences in student evaluation comparing to the previous curriculum. Although they tried to overcome these problems one by one, this should be a topic of concern for researchers in other articles and education observers to evaluate the curriculum. Hopefully, this research can help educators to come up with solutions to these problems.